ISSUES OF DEVELOPING READING LITERACY BASED ON DIGITAL LEARNING TOOLS (World Conference on Agricultural and Earth Sciences, 2026)
This article analyzes the role and importance of digital educational tools in developing reading literacy. It highlights the potential of e-textbooks, video lessons, audiobooks, interactive platforms, and multimodal texts in fostering students’ abilities to search, analyze, evaluate, and apply information in real-life contexts. The methodological aspects of developing reading literacy in a digital environment are also discussed in accordance with the requirements of international assessment programs such as PISA and PIRLS.
Keywords: digital educational tools, reading literacy, multimodal text, interactive platforms, PISA, PIRLS, information analysis, digital environment, functional literacy.